Analisis kepuasan konsumen terhadap kualitas layanan jaringan distribusi PT. XYZ Kabupaten dan Kota Probolinggo - Andrew Setiawan Rusdianto; Bambang Herry Purnomo; Ida Bagus Suryaningrat; Dani Prasetyo (AGROINTEK, 2024)
The need for fertilizer in the agricultural sector is critical as one of the keys to soil fertility. PT. XYZ is a company engaged in the fertilizer, chemical and agribusiness industries which has a network of authorized kiosks. A decrease in the number of kiosks in the distribution network area of Probolinggo Regency dan City may indicate that the services provided by the company still do not meet the expectations of consumers, resulting in a decrease in consumer satisfaction. This study aimed to determine the attributes of service quality, and the level of customer satisfaction based on the servqual attribute on service quality and compile recommendations for service improvement in the distribution network at PT. XYZ of Probolinggo Regency dan City. The analytical method used was the servqual method to identify and determine the condition of service quality with five servqual dimensions and the Importance Performance Analysis (IPA) method to obtain priority service attributes. The results showed that there were 3 service attributes has positive GAP and 23 service attributes had negative GAP values. The mapping used the Importance Performance Analysis quadrant obtained 5 service attributes in quadrant A (Top Priority), 7 service attributes in quadrant B (Maintain Service), 7 service attributes in quadrant C (low priority), and 7 service attributes in quadrant D (Excessive). Recommendations for improvements that can be made based on the attributes in quadrant A (Top Priority).